Revitalization of Hakeng (Traditional Prohibitions) and the Concept of Traditional Fines in the Draft Village Regulations Concerning the Protection of Marine Biota from Exploitation in Harilolong East Pura : Revitalization of Hakeng (Traditional Prohibitions) and the Concept of Traditional Fines in the Draft Village Regulations Concerning the Protection of Marine Biota from Exploitation in Harilolong East Pura - Pandu Sula, Ibrahim; Killa, Rudi Krisyanto Lema; Lakalet, Lestari; Laoepada, Setia Budi; Peny, Theresia Lounggina Luisa (Vivabio: Jurnal Pengabdian Multidisiplin, 2024)
This community service is a service carried out based on the results of research conducted previously. Research with the hypothesis that there is a need for revitalization of Hakeng or that traditional prohibitions can be adopted in the application of sanctions that are the same as the administrative sanctions contained in the draft Village Regulations. The approach used is to use a qualitative method approach with the concept of case studies and an empirical juridical approach focusing on the application of customary law. The implementation of the service uses the concept of forum group discussion (FGD) by presenting representatives of village officials and representatives of indigenous communities who are directly related to the scope of the problem. The material discussed relates to the existence of Hakeng or customary prohibitions today, determining the concept of implementing Hakeng and administrative sanctions in the draft Village Regulations, and procedures and mechanisms for their implementation. The results of the group discussion forum emphasize several points, namely: first, the concept of Hakeng or traditional prohibitions is still recognized for its existence and strength of religious magic and has strong traditional values, so care needs to be taken in its implementation. For this reason, Hakeng contains heavy sanctions, the traditional Hila Lele prohibition sign is used as a reminder; secondly, in the draft village regulations regarding the protection of marine biota from exploitation, the sanctions imposed are administrative sanctions in the form of fines with different rupiah amounts between the Harilolong indigenous community and people/groups of people from outside the village or foreigners, payment of fines is determined based on fishing activities which have been determined and mutually agreed upon; third, agreement on these points is absolute and must be stated in the draft Village Regulations during the discussion agenda and followed by determination ABSTRAK Pengabdian masyarakat ini merupakan pengabdian yang dilaksanakan berdasarkan hasil penelitian yang dilakukan pada waktu sebelumnya. Penelitian dengan hipotesa bahwa perlu adanya revitalisasi Hakeng atau larangan adat sekiranya dapat diadopsi dalam penerapan sanksi yang kedudukanya sama dengan sanksi administrasi yang termuat pada rancangan Peraturan Desa. Metode pendekatan yang dilakukan adalah dengan menggunakan pendekatan metode kualitatif  dengan konsep case studies dan pendekatan yuridis empiris dengan berfokus pada penerapan hukum adat. Pelaksanaan pengabdian menggunakan konsep forum group discusion (FGD) dengan menghadirkan keterwakilan perangkat desa dan keterwakilan masyarakat adat yang berhubungan langsung dengan ruang lingkup permasalahan. Materi yang didiskusikan berhubungan dengan eksistensi Hakeng atau larangan adat pada masa sekarang, penentuan konsep penerapan Hakeng dan sanksi administrasi dalam rancangan Peraturan Desa, dan prosedur serta mekanisme pelaksanaanya. Hasil dari forum group discussion menekankan pada beberapa poin yakni : pertama, konsep Hakeng atau larangan adat masih diakui keberadaan dan kekuatan religious megic-nya dan memiliki nilai adat yang kuat, sehingga perlu kehati-hatian dalam pemberlakuannya. Untuk itu dengan Hakeng mengandung sanksi yang berat maka digunakan tanda larangan adat Hila Lele sebagai pengingatan; kedua, dalam rancangan peraturan desa mengenai perlindungan biota laut dari eksploitasi, sanksi yang diberlakukan adalah sanksi administrasi dalam bentuk denda dengan besaran nilai rupiah yang berbeda antara masyarakat adat Harilolong dan orang/kelompok orang dari luar desa atau orang asing, pembayaran denda ditentukan berdasarkan aktifitas melaut yang telah ditentukan dan disepakati bersama; ketiga, kesepakatan poin-poin ini menjadi mutlak dan harus tertuang dalam rancangan Peraturan Desa saat agenda pembahasan dan dilanjutkan pada penetapan.